2019
DOI: 10.3390/agronomy9070362
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Canopy Size and Yield of Rayong 9 Cassava Genotype under Rainfed and Irrigated Conditions

Abstract: The objectives of this study were to investigate the effect of seasonal variation on canopy size, and the effect of canopy size on light penetration of ‘Rayong 9′ cassava under irrigated and rainfed conditions. Rayong 9 was planted under two water regimes in a randomized complete block design with four replications in May and November for two years. At final harvest, years were significantly different (p ≤ 0.05) for biomass, shoot dry weight, and harvest index and contributed to large portions of total variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Planting dates accounted for the largest proportion of variation for most cassava traits (38.2%-60.8%), except for starch content, which was greatly affected by water regimes (52.1%). These results were similar to a previous investigation of cassava biomass and storage root yield reported by Mahakosee et al [22]. They reported that planting date had a greater effect in comparison to water regimes and planting date by water regime interactions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Planting dates accounted for the largest proportion of variation for most cassava traits (38.2%-60.8%), except for starch content, which was greatly affected by water regimes (52.1%). These results were similar to a previous investigation of cassava biomass and storage root yield reported by Mahakosee et al [22]. They reported that planting date had a greater effect in comparison to water regimes and planting date by water regime interactions.…”
Section: Discussionsupporting
confidence: 92%
“…Studies by El-Sharkawy et al [31] and Saithong et al [32] indicated that a temperature range between 25 to 35 • C during early to mid-growth stages is optimum for cassava crop growth and results in increased activities of the enzymes involved in photosynthesis and the synthesis of starch. High temperatures and high solar radiation during the early to mid-growth stages also increased canopy size, leaf growth rate and leaf area index [22,33,34].…”
Section: Discussionmentioning
confidence: 97%
“…In Asia, the early growth stages of cassava planted during the early rainy season will be subjected to higher rainfall, temperature, RH and SR than those planted in the late rainy season. However, drought will often hit early rainy season plantings when they are in the later growth stages, reducing canopy size (CS) and yield [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These factors affect the change in canopy of cassava and cassava genotypes respond differently to environmental changes. While the responses of CS on seasonal variation under different water regimes had been reported, they generally use only one genotype [11]. Therefore, the objective of this study was to determine canopy architecture, light penetration and photosynthesis of three cassava genotypes under different seasonal variations.…”
Section: Introductionmentioning
confidence: 99%
“…It was clearly evident that lower values of simulated total crop and storage root dry weights for planting dates in May, June, July, August, and September could be explained by lower total amounts of rainfall during the growth stages of high above-ground development and high carbohydrate translocation to the storage root (Table 5). In a recent field experiment in Thailand under rainfed conditions, Mahakosee et al [52] found that a dry period during the late growing stages of cassava planted in May resulted in lower total crop biomass and storage root dry weights of the Rayong 9 genotype than for the December planting date. Growth stage 1 = leaf development and formation of root system (0-3 months after planting); Growth stage 2 = development of stems and leaves (3-6 months after planting); Growth stage 3 = high carbohydrate translocation to the roots (6-10 months after planting); Growth stage 4 = declining phase (10-12 months after planting); all four cassava growth stages were described by Alves [53].…”
Section: The Interaction Between Planting Dates and Water Regimesmentioning
confidence: 99%